Nuclear actin filaments recruit cofilin and actin-related protein 3, and their formation is connected with a mitotic block - Kalendová, Alžběta; Kalasová, Ilona; Yamazaki, Shota; Uličná, Lívia; Harata, Masahiko; Hozák, Pavel (Histochemistry and cell biology, 2014)
Although actin monomers polymerize into filaments in the cytoplasm, the form of actin in the nucleus remains elusive. We searched for the form and function of β-actin fused to nuclear localization signal and to enhanced yellow fluorescent protein (EN-actin). Our results reveal that EN-actin is either dispersed in the nucleoplasm (homogenous EN-actin) or forms bundled filaments in the nucleus (EN-actin filaments). Formation of such filaments was not connected with increased EN-actin levels. Among numerous actin-binding proteins tested, only cofilin is recruited to the EN-actin filaments. Overexpression of EN-actin causes increase in the nuclear levels of actin-related protein 3 (Arp3). Although Arp3, a member of actin nucleation complex Arp2/3, is responsible for EN-actin filament nucleation and bundling, the way cofilin affects nuclear EN-actin filaments dynamics is not clear. While cells with homogenous EN-actin maintained unaffected mitosis during which EN-actin re-localizes to the plasma membrane, generation of nuclear EN-actin filaments severely decreases cell proliferation and interferes with mitotic progress. The introduction of EN-actin manifests in two mitotic-inborn defects-formation of binucleic cells and generation of micronuclei-suggesting that cells suffer aberrant cytokinesis and/or impaired chromosomal segregation. In interphase, nuclear EN-actin filaments passed through chromatin region, but do not co-localize with either chromatin remodeling complexes or RNA polymerases I and II. Surprisingly presence of EN-actin filaments was connected with increase in the overall transcription levels in the S-phase by yet unknown mechanism. Taken together, EN-actin can form filaments in the nucleus which affect important cellular processes such as transcription and mitosis.
Keywords: Luminescent Proteins; mikrofilamenta; RNA-polymerasa I; Cell Line, Tumor; HEK293 Cells; RNA Polymerase I; bakteriální proteiny; Bacterial Proteins; Transcription, Genetic; lidé; Cell Nucleus; protein 3 související s aktinem; faktory depolymerizující aktin; HEK293 buňky; Mitosis; mitóza; buněčné jádro; Humans; genetická transkripce; Actin-Related Protein 3; luminescentní proteiny; aktiny; Actins; restrukturace chromatinu; RNA-polymerasa II; Actin Depolymerizing Factors; RNA Polymerase II; Actin Cytoskeleton; nádorové buněčné linie; Chromatin Assembly and Disassembly